Factors that affect successful implementation of community infrastructure projects : the case of Makhuduthamaga Local Municipality, Limpopo Province - Segale, Matsedi Albert (My University, 2015)
Rural communities in South Africa, including Makhuduthamaga Local Municipality, experience mobility problems in order to access facilities like hospitals, police stations, schools and shopping centres. This research study attempted to identify factors that affect effective implementation of community road infrastructure projects under the jurisdiction of Makhuduthamaga Local Municipal Council. The study was qualitative in nature wherein municipal officials directly involved in provision and maintenance of road infrastructure in the municipality, ward councillors and a consultant were interviewed. The study wanted to understand how councillors, officials and consultant observe service delivery in terms of road infrastructure in the area. The respondents indicated that the project management unit is trying very hard to ensure that service provision is spread adequately but the challenges experienced hamper effective service delivery. The identified challenges include: interference, including political interference of some stakeholders, service providers who are not experienced enough, inadequate finances and supply chain systems and policies which seem to be ill-defined and/or not implemented properly. There is a need for the government to invest more in infrastructure, specifically roads. It was proven from the findings of this study that the government still has to do more in providing quality roads in rural areas. The municipality should prioritise financial allocation or provision for road infrastructure in their budget to help in the stimulation of the burden experienced by everyone in this regard. The study recommends that the Project management unit needs to adhere to policy and contracts that bind service providers. There should be training of officials and service providers to improve the quality and effectiveness of the services rendered.
Thesis (MBA.) -- University of Limpopo, 2015
Keywords: Communuty development projects; Road infrastructure projects; Local government; Municipal government; Community development -- South Africa -- Limpopo; Rural development -- South Africa -- Limpopo; Local government -- South Africa -- Limpopo